Pemanfaatan Limbah Cair Tahu (Whey Tahu) Sebagai Media Tumbuh Acetobacter xylinum untuk Memproduksi Nata - Muhammad Alwi; Rahmiati Rahmiati; Umrah Umrah (Biocelebes, 2011)
Research on “Waste Utilization Tahu” (Whey Tahu) as growth media for producing nata Acetobacter xylinum has been carried out from February to March 2011 with the aim of utilizing wastewater tahu (whey tahu) as a growing medium nata-producing Acetobacter xylinum as a source food and sucrose concentration and pH optimal for the growth of bacteria A. xylinum in producing nata. Method used in this research is experiment by 9 combinations of treatments and 3 repeation. Design was using a “Completely Randomized with composed with factorial” the factors is sugar concentration and secondary factor is acidity level (pH) . The Result of research indicate that nata and thick and also different at all of given treatments. The interaction between sucrose and pH provide a response to differences in thickness of nata formed. The best treatment which is interaction of sugar 10% and pH 5 in thick forming nata that is and 0,43 cm. and rendemen nata 15.92%. Key words: Whey tahu, Acetobacter xylinum, and Nata.